Resources for the Study of the Personality of ‘Abd Allāh al-Baṭṭāl (85-121 AH / 703-739 AD) - Meer, Yousif Ahmed Mohamed; Okleh, Issam Mustafa (Jordan Journal for History and Archaeology, 2024)
This study identifies the sources of information about ‘Abd Allāh al-Baṭṭāl, a military figure in the Umayyad period who played an important role in fighting the Byzantine Empire and protecting the frontiers of the Levant and thereby forming a heroic persona in the popular imagination in the Levant. The article examines those sources and the reasons why Iraqi sources ignore him. Much of the Levantine sources of the early Islamic period have been lost, which along with the Iraq-centric focus of the Abbasid historians have resulted in a major lack of information about him